Dualidade brutalista: violência e moralismo na obra de Rubem Fonseca - Rubens Fernandes Corgozinho Júnior (2023)
The present works starts from a study of Rubem Fonseca’s work comprehended by his three firsts short story volumes released within the 1960’s (Os prisioneiros, 1963, A coleira do cão, 1965, e Lúcia McCartney, 1969). In this initial moment, it was seeked to analyze how the themes of violence and moralism are present as remarkable characteristics of the production, once that the first of these elements a central mark of Fonseca’s poethic that would be insistently appointed by the 1970’s critics. By the reading of the short stories, the work intends to identify different forms of manifestation of the mentioned pair in the narratives starred by Fonseca’s typical characters, underground individuals or involved, somehow, with the marginality and with the practice of transgression. For that purpose, there are mobilized knowledges from the philosophy field, by thinkers such as Friedrich Nietzsche, Georges Bataille and Hannah Arendt, as well as culture thinkers as Sigmund Freud and René Girard. The initial understanding is that there would be a particular way of working with violence and moralism adopted in the inaugural works of Fonseca that would be different from the one that would be adopted later, so that it’s possible to think a relation of continuity within the production, in a way that it would happen, over the years, a growing thematization of the violence, coinciding, somehow, with the hardening of the Military Regime's, started in 1964, practices.